Turbo-machinery dynamics design and operation - Rangwala, A. S. (McGRAW-Hill New York, 2005)
This comprehensive text presents a detailed treatment of the design, development, and operation of turbo-machinery. Starting with the fundamentals of thermodynamics and cycle design and ending with the latest trends in the development and production of many different types of turbo-machines, the author provides in-depth methods for analyzing new design procedures and maximizing structural integrity and operating efficiency that will assist in the design and analysis of even more powerful and efficient turbo-machinery.
Keywords: Turbines -- Design and construction